Peranan Komunikasi Keluarga Dalam Mempertahankan Semangat Hidup Penyintas Miastenia Gravis - Rafi, M. Soulthan; Nursanti, Siti; Utamidewi, Wahyu (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Myasthenia gravis is a nerve-attacking disease that can cause survivors to fear of what they are facing. This disease can be said to be quite rare and it is not uncommon for survivors to die, this can trigger the loss of the survivors' zest for life. The purpose of this research is to analyze the role of the family plays in maintaining the esprit of myasthenia gravis survivors. This study uses Viktor Frankl's logotherapy theory and semantic theory. In this study, the method that used is a qualitative research method with a case study approach.. The results of this study appearence that the family has an important role in maintaining the survivors' zest for life. Several cases that have occurred Survivors can feel better if the role of the family is carried out well, this can be seen from the changes felt by survivors. Those who initially felt a lack of enthusiasm for life until they finally felt the enthusiasm to return to live life as usual, even to be able to make peace and live side by side with the illness they felt. Keywords: Family Communication, Lively Spirit, Myasthenia Gravis